2012
DOI: 10.1007/s12032-012-0348-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the clinico-hematological relevance of the breakpoint location within M-BCR in chronic myeloid leukemia

Abstract: The Philadelphia chromosome (Ph) derives from the balanced translocation between chromosomes 9 and 22. This chromosomal translocation results in the fusion between the 5' part of the BCR gene, normally located on chromosome 22, and the 3' part of the ABL gene on chromosome 9 giving origin to a BCR-ABL fusion gene which is transcribed and then translated into a hybrid protein. In general, three breakpoint cluster regions in the BCR gene have been described: major (M-BCR), minor (m-BCR) and micro (μ-BCR). Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
33
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 38 publications
7
33
0
Order By: Relevance
“…Regarding the main variables at diagnosis, results in our patient group are similar to those already published (Barboza et al, 2000;Bennour et al, 2013;Smith et al, 2014). In agreement with published data, our study showed a statistically significant association between the e14a2 transcript and high platelet count (Bennour et al, 2013), but also between the e13a2 transcript with high leukocyte count (Hanfstein et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Regarding the main variables at diagnosis, results in our patient group are similar to those already published (Barboza et al, 2000;Bennour et al, 2013;Smith et al, 2014). In agreement with published data, our study showed a statistically significant association between the e14a2 transcript and high platelet count (Bennour et al, 2013), but also between the e13a2 transcript with high leukocyte count (Hanfstein et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with published data, our study showed a statistically significant association between the e14a2 transcript and high platelet count (Bennour et al, 2013), but also between the e13a2 transcript with high leukocyte count (Hanfstein et al, 2014). The statistical analysis for the e13a2/e14a2 was not possible, due to the small number of patients with this transcript (N = 5).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The transcript distribution in CML has been reported in European and some other populations with frequencies for b2a2 and b3a2 transcripts being nearly of the order of 40% and 55% [10][11][12][13], which is relatively close to the previous from Iran report [8] and our study. However, a study on an Ecuadorian population, showed very different frequencies: 5% for b3a2 and 95% for b2a2 [6].…”
Section: Discussionsupporting
confidence: 91%
“…19 Types of breakpoint is related to the clinical manifestation of CML patients. 24 Patients with major breakpoint type is characterized with neoplastic expansion in myeloid and megacaryocytic, as well as differentiation failure and moderate degree of maturation on granulocyte progenitor. Patients who carry minor type BCR-ABL gene showed monocytosis.…”
Section: Breakpoint Typementioning
confidence: 99%